Aktualisasi Kaidah Fikih al-Muslimūna ‘alā Syurūṭihim dalam Transaksi Jual Beli - Kasman Bakry; Ihwan Wahid Minu; Akhmad Hanafi Dain Yunta; Hasyim Hasyim (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2021)
This research aims, namely: first, to describe the concept of the rules of jurispruding al-muslimūna 'alā syurūtihim; Second, describe the actualization of the rules in everyday buying and selling transactions. To reason the study, it is used this type of literature research (library research) with normative approach methods and content analysis whose focal point is on the study of manuscripts and texts related to research problems. The results of the study found that: first, the concept of the rule of jurisprudent al-muslimūna 'alā syurūtihim is easy and concise in its pelafazan and has a wide legal scope and has a basic determination of both the Qur'an and hadith; Second, the rule of jurispruding al-muslimūna 'alā syurūtihim is required in the establishment of the legal conditions in buying and selling transactions. By implication, practitioners of Islamic law can easily decide on several issues in the field of Islamic law.